A Case Report of Pulsed Radiofrequency Plus Suboccipital Injection of the Greater Occipital Nerve: An Easier Target for Treatment of Cluster Headache - Belgrado, Enrico; Surcinelli, Andrea; Gigli, Gian Luigi; Pellitteri, Gaia; Dalla Torre, Chiara; Valente, Mariarosaria (Frontiers in Neurology, 2021)
Introduction: In cluster headache, the efficacy of suboccipital steroid injection is notable within a few days, unless few data are available about the duration of efficacy. A combination treatment, consisting of suboccipital steroid injection plus pulsed radiofrequency, could potentially lead to a long-term benefit. Evidence about pulsed radiofrequency of the greater occipital nerve is lacking. Patients and methods: We retrospectively describe a series of four cluster headache patients treated with suboccipital steroid injection plus pulsed radiofrequency of the greater occipital nerve. Results: All patients achieved a 50% reduction in attacks frequency in the seven days after the first treatment. Moreover, a long pain-free remission period up to 15 months was noted. Conclusion: Suboccipital steroid injection plus pulsed radiofrequency of the greater occipital nerve might have both acute and prophylactic effects in cluster headache. Greater occipital nerve is more accessible to pulsed radiofrequency than other targets.